Identification of Potential Genotype Influencing Stress Tolerance to Fe Toxicity and P Deficiency under Low Land Acidic Soils Condition of North Eastern Rice, “Shasarang” - Das, Sudip; Tyagi, Wricha; Rai, Mayank; Debnath, Ashim (International Journal of Bio-resource and Stress Management, 2017)
P is one of the macronutrients required for plant growth and development, whereas Fe is a micronutrient required for various metabolic functions of plant. However, under acidic soil conditions, due to low pH Fe2+ toxicity and P deficiency occurs leading to decrease in crop productivity. The present investigation was undertaken to understand molecular physiology of acidity tolerance with special reference to P-deficiency and Fe-toxicity tolerance in Shasarang (LR11). Under lowland acid soils (pH=5.2), KMR3 showed a higher bronzing score of 3 at 110 DAT and LR11 showed very little or no bronzing. The field performance of LR11 was better as compared to KMR3 with respect to yield related traits. Furthermore, our data confirmed that LR11 is infact Fe toxicity tolerant and “Shasarang” means “tolerant to Fe” in Khasi. The susceptible genotype, KMR3, showed significant decrease in shoot and root dry weight under low P and Fe toxicity conditions in hydroponic. However, in LR11, the difference in root-shoot dry weight in control and treatment were not significant. Excess amounts of iron in hydroponics could lead to distinct variation in the bronzing score, root-shoot biomass. Based on this criteria Nipponbare has been considered tolerant and Kasalath as susceptible. In our case, screening using excess of Fe and low P simultaneously, Kasalath performed at par with LR11. This study, therefore, suggests that identified tolerant LR11 can be a potential target for enhancing rice production introducing tolerance to acidity under lowland rainfed field conditions.